2023
DOI: 10.1128/aac.00683-23
|View full text |Cite
|
Sign up to set email alerts
|

Drug interaction potential of high-dose rifampicin in patients with pulmonary tuberculosis

Ralf Stemkens,
Veronique de Jager,
Rodney Dawson
et al.

Abstract: Accumulating evidence supports the use of higher doses of rifampicin for tuberculosis (TB) treatment. Rifampicin is a potent inducer of metabolic enzymes and drug transporters, resulting in clinically relevant drug interactions. To assess the drug interaction potential of higher doses of rifampicin, we compared the effect of high-dose rifampicin (40 mg/kg daily, RIF40) and standard-dose rifampicin (10 mg/kg daily, RIF10) on the activities of major cytochrome P450 (CYP) enzymes and P-glycoprotein (P-gp). In thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Rifampicin mediation primarily occurs via its action on PXR . Studies have shown that rifampicin can induce dozens of genes in the CYP450 family, including CYP3A4, CYP2C9, CYP2D6, CYP2A13, and CYP24A1, among others. , There are also studies suggesting that rifampicin can induce ABCB1 (P-gp), but another study suggests that rifampicin may inhibit P-gp . There are important species differences in the ligand preferences of these xenobiotic-sensing receptors .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rifampicin mediation primarily occurs via its action on PXR . Studies have shown that rifampicin can induce dozens of genes in the CYP450 family, including CYP3A4, CYP2C9, CYP2D6, CYP2A13, and CYP24A1, among others. , There are also studies suggesting that rifampicin can induce ABCB1 (P-gp), but another study suggests that rifampicin may inhibit P-gp . There are important species differences in the ligand preferences of these xenobiotic-sensing receptors .…”
Section: Discussionmentioning
confidence: 99%
“…48,49 There are also studies suggesting that rifampicin can induce ABCB1 (P-gp), 50 but another study suggests that rifampicin may inhibit P-gp. 48 There are important species differences in the ligand preferences of these xenobiotic-sensing receptors. 51 In this study, it was found that the genes induced by rifampicin in A. farreri are quite distinct from those in human and other vertebrate experiments (Table S3).…”
Section: The Effect Of the First Application Of An Inducer To Metabolizementioning
confidence: 99%